Comparative study of antioxidant and antibacterial activities in the methanol and ethyl acetate extract of leaf and stem bark of Semecarpus anacardium Linn. - Bhatt, Bishan Datt; Chhetry, Chandradip (Journal of Nepal Chemical Society, 2018)
Available with fulltext.